Primary Cutaneous Anaplastic Large Cell Lymphoma—A Review of Clinical, Morphological, Immunohistochemical, and Molecular Features - Ortíz Hidalgo, Carlos Federico; Pina-Oviedo, Sergio (MDPI, 2023)
Primary cutaneous anaplastic large cell lymphoma (ALCL) is the second most common cutaneous T-cell lymphoma after mycosis fungoides and belongs to the spectrum of cutaneous CD30+ T-cell lymphoproliferative disorders. Although primary cutaneous ALCL usually presents as a localized nodule or papule with or without ulceration, multifocal lesions may occur in up to 20% of cases. Histologically, primary cutaneous ALCL consists of a diffuse dermal infiltrate of medium to large anaplastic/pleomorphic cells with abundant amphophilic-to-eosinophilic cytoplasm, horseshoe-shaped nuclei, strong and diffuse expression of CD30, and with focal or no epidermotropism. The neoplastic infiltrate may show angiocentric distribution and may extend to the subcutis. Patients with localized or multifocal disease have a similar prognosis with a 10-year overall survival rate of 90%. Approximately 30% of primary cutaneous ALCLs harbor a DUSP22 (6p25.3) gene rearrangement that results in decreased expression of this dual-specific phosphatase, decreased STAT3 activation, and decreased activity of immune and autoimmune-mediated mechanisms regulated by T-cells. © Cancers
Keywords: ALK; CD30; DUSP22; Cutaneous T-cell lymphomas; Immunohistochemistry; Primary cutaneous anaplastic large cell lymphoma